THE INFLUENCE OF BANKING HEALTH LEVELS BY USING RGEC METHOD ON BANKING FINANCIAL PERFORMANCE - Wijaya, Lareina; Imelda, Elsa (Graduate Program of Universitas Tarumanagara, 2025)
Financial performance being a sentimental sense of company’s financial to facilitate bank management and investment decisions for mitigate risk and strengthen profitability. This study aim to analyze and to examine the impact of RGEC method on the profit growth of companies listed on IDX in five periods, 2019-2023. Determination of the sample by using the method of purposive sampling. The type of research used is quantitative using secondary data that acquired from company’s annual reports from 2019 to 2023 periode with a total sample selected about 42 banking companies. The tool used is multiple linear regression assisted by eviews13. Results obtained in the research indicate that RGEC significantly impacted companies profit growth in 2019-2023 period. Risk profile proxied with non performing loan and good corporate governance proxied with board of independent commissioners has negative impact on profit growth. On the other side, capital proxied by capital adequacy ratio positively impact on companies profit growth. Whereas earnings proxied by net interest margin does not affect banking profit growth listed on IDX during 2019 and 2023.